Profit from the positive proven leadership strategies to boost productivity and transform your business - Margaret Greenberg and Senia Maymin, Performed by Eli Woods (Grand Haven, Michigan McGraw-Hill Education on Brilliance Audio, 2014)
You're constantly challenged to grow your business, increase productivity, and improve quality--all while reducing or keeping budgets flat. So what's a managerto do.
Keywords: Leadership